2013
DOI: 10.1002/cjce.21919
|View full text |Cite
|
Sign up to set email alerts
|

Stability of slot‐rectangular spouted beds with multiple slots

Abstract: Stability of the spouting in slot-rectangular spouted beds with multiple compartments and slots is investigated and compared with a single-chamber, single-slot spouted bed. Several different configurations of multiple slots were tested, including parallel and aligned, with gas drawn from a common plenum chamber. The stability of the spouting was observed visually and identified by the evolution of pressure drop and its fluctuation. The stability of multiple spouting was found to be mainly affected by the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Chen et al [246] simulated a multiple spout fluidised bed assessing the effect of baffles, which divide the bed in three parts. They showed the effect was different depending on the number of gas inlet used: positive in case of double and triple spouting and negative in case of single spouting; moreover, in case of multiple spouting, the fountains may disturb each other creating more difficulties in the development of a stable regime.…”
Section: Tfm Applied To Auxiliary Devicesmentioning
confidence: 99%
“…Chen et al [246] simulated a multiple spout fluidised bed assessing the effect of baffles, which divide the bed in three parts. They showed the effect was different depending on the number of gas inlet used: positive in case of double and triple spouting and negative in case of single spouting; moreover, in case of multiple spouting, the fountains may disturb each other creating more difficulties in the development of a stable regime.…”
Section: Tfm Applied To Auxiliary Devicesmentioning
confidence: 99%
“…In addition, they noted an increase of 3D effects when the bed height or the column thickness increased. Chen et al [20] investigated the effect of multiple spouting in rectangular spouted beds and concluded that scale-up could be obtained with rectangular chambers separated by suspended partition baffles.…”
Section: -Introductionmentioning
confidence: 99%
“…Moreover, the evolution of pressure drop and its fluctuation has long been regarded as an indicator for the spouting quality. 23 Pietsch et al 24 analyzed the spouting stability by time-dependent pressure drop behavior and investigated the effect of the draft plate on the alternating deflection of the spout in the lateral direction. However, due to the intrinsic defects of the detection methods, these studies can only provide a general judgment about whether the spout deflection happens and cannot offer the fundamental understanding of the spout deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong and Zhang built a relationship between the flow pattern and entropy of the pressure drop. Moreover, the evolution of pressure drop and its fluctuation has long been regarded as an indicator for the spouting quality . Pietsch et al analyzed the spouting stability by time-dependent pressure drop behavior and investigated the effect of the draft plate on the alternating deflection of the spout in the lateral direction.…”
Section: Introductionmentioning
confidence: 99%